2021
DOI: 10.3389/fimmu.2021.750114
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Interleukin-18 as a Diagnostic Biomarker to Differentiate Adult-Onset Still’s Disease With/Without Macrophage Activation Syndrome From Other Secondary Hemophagocytic Lymphohistiocytosis in Adults

Abstract: BackgroundInterleukin (IL)-18 is markedly elevated in systemic inflammatory diseases that cause the ‘cytokine storm’ such as adult-onset Still’s disease (AOSD) and hemophagocytic lymphohistiocytosis (HLH). The differences in IL-18 between AOSD and HLH, especially in adults, is uncertain. Macrophage activation syndrome (MAS), a form of secondary HLH, is often difficult to differentiate cases of AOSD that include MAS from other secondary HLH. In this case-control study, we investigated whether serum IL-18 levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
1
22
0
1
Order By: Relevance
“…We reported that the serum IL-18 levels were significantly higher in patients with AOSD (with or without MAS) compared to patients with HLH secondary to other causes, including SLE ( 27 ), and we also observed that a serum IL-18 level >18,550 pg/mL could be used to distinguish between AOSD and HLH with 90.3% sensitivity and 93.5% specificity. Our patient’s remarkably high serum IL-18 level (161,221 pg/mL) was suggestive of AOSD.…”
Section: Discussionmentioning
confidence: 53%
“…We reported that the serum IL-18 levels were significantly higher in patients with AOSD (with or without MAS) compared to patients with HLH secondary to other causes, including SLE ( 27 ), and we also observed that a serum IL-18 level >18,550 pg/mL could be used to distinguish between AOSD and HLH with 90.3% sensitivity and 93.5% specificity. Our patient’s remarkably high serum IL-18 level (161,221 pg/mL) was suggestive of AOSD.…”
Section: Discussionmentioning
confidence: 53%
“…The 28-day mortalities were 0%, 4.5 ± 4.4%, 4.0 ± 3.9%, and 17.9 ± 3.6% for EBV-HLH patients in the LLQ, LUQ, RUQ, and RLQ (p = 0.034), and the 5-year OS rates were 94.1 ± 5.7%, 81.1 ± 8.6%, 70.4 ± 9.5%, and 74.7 ± 7.1% (p = 0.24), respectively. differentiating HLH from infections or other inflammatory entities (13)(14)(15)(16). The present study shows that different subtypes of HLH present distinct cytokine patterns.…”
Section: Distinct Features Of Hlh Patients In a Four-quadrant Modelmentioning
confidence: 50%
“…HLH is a rapidly fatal disease caused by an immune dysregulation characterized by hypercytokinemia and overactivation of T cells and macrophages. Many inflammatory cytokines including IFN-γ, IL-6, IL-10, IL-12, IL-18, TNF-α, and CXCL9 are elevated in patients with HLH, and the cytokine patterns are helpful in differentiating HLH from infections or other inflammatory entities ( 13 16 ). The present study shows that different subtypes of HLH present distinct cytokine patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Javaux et al have published different parameters that are useful for distinguishing HLH and AOSD flare, including lower fibrinogen, leukocyte and platelet counts, but no difference in GF fraction [ 7 ]. Another study showed that interleukin (IL)-18 levels have high accuracy for the differential diagnosis of AOSD and HLH but IL-18 is rarely available routinely [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike GF, total serum ferritin (TSF) has been repeatedly reported as a hallmark of AOSD, mostly for extreme values [ 16 , 17 , 18 ]. However, TSF lacks sensitivity and specificity [ 19 ].…”
Section: Introductionmentioning
confidence: 99%